Spiritualization of Child Education in the Qur'anic Sufism Perspective in the Covid-19 Era - Muh. Mustakim; Kana Safrina Rouzi; Tumin Tumin (International Journal of Islamic Educational Psychology, 2021)
The COVID-19 pandemic has implications for changing the attitudes and behavior of the world community, including in the field of education. The Indonesian government, in this case, has decided to study from home (BDR) for schools to universities in addition to the work from home (WFH) policy. BDR challenges have both advantages and disadvantages. Among the weaknesses that need to be watched out for is the burnout of children in online learning from home, which cannot be denied because similar conditions are also experienced by parents, which erode the enthusiasm for learning to spirituality in the family. Therefore, this paper examines how to reconstruct the spiritualization of education for children in families amid COVID-19. This qualitative research used a descriptive approach, describing the data obtained from the interpretation of the term "tazkiyah" in the Qur’an and verses related to children's education to be contextualized into building the spiritualization concept of children's education in the perspective of Qur'anic Sufism. As part of the literature research, the data analysis adopted Gadamer's hermeneutics developed by Fakhrudin Faiz that hermeneutics revolves around text, context, and contextualization. The results showed that parents have a major role in children's education amid COVID-19 as the prominent educators in the family. These findings corroborate the opinions of Comenius, Nasih Ulwan, Abdurrahaman An-Nahlawi, and Ki Hajar Dewantara about the importance of family education. The spiritualization of children's education in the perspective of Quranic Sufism integrates the three theologies in religion as proposed by Barbour, namely the theology of revelation, natural theology, and religious experience. Therefore, the spiritualization of children's education is a necessity.